Kinetics of Remazol Black B adsorption onto carbon prepared from sugar beet pulp - Dursun, Arzu Y.; Tepe, Ozlem; Uslu, Gulsad; Dursun, Gulbeyi; Saatci, Yusuf (Springer Heidelberg, 2013)
Dried sugar beet pulp, an agricultural solid waste, was used for the production of carbon. Carbonised beet pulp was tested in the adsorption of Remazol Black B dye, and adsorption studies with real textile wastewater were also performed. Batch kinetic studies showed that an equilibrium time of 180 min was needed for the adsorption. The maximum dye adsorption capacity was obtained as 80.0 mg g(-1) at the temperature of 25 degrees C at pH = 1.0. The Langmuir and Freundlich adsorption models were used for the mathematical description of the adsorption equilibrium, and it was reported that experimental data fitted very well to the Langmuir model. Mass transfer and kinetic models were applied to the experimental data to examine the mechanisms of adsorption and potential rate-controlling steps. It was found that both external mass transfer and intraparticle diffusion played an important role in the adsorption mechanisms of dye, and adsorption kinetics followed the pseudo-second-order type kinetic model. The thermodynamic analysis indicated that the sorption process was exothermic and spontaneous in nature.
Keywords: Adsorption; Beet pulp carbon; Remazol Black B; Kinetics; Intraparticle diffusion model; External mass transfer model